Sistema simplificado de bajo costo para la recolección y uso de las aguas lluvias para bebederos de ganado (2024)
This project is geographically located in the municipality of Ubaté, where it´s economy is primarily based on livestock farming, commerce of dairy products and mining. The sustainability of these practices requires a high-water consumption; therefore, this study proposes a rainwater harvesting system, which includes a catchment surface, conveyance systems, treatment and isolated storage to maintain water safety. This design is made from historical hydrological records. and utilizes local raw materials to reduce costs to make it a profitable investment for the rural population in the region